A new species of the Gekko japonicus group (Squamata: Sauria: Gekkonidae) from the border region between China and Vietnam - Nguyen, Truong Quang; Wang, Ying-Yong; Yang, Jian-Huan; Lehmann, Tanja; Le, Minh Duc; Ziegler, Thomas; Bonkowski, Michael (Zootaxa, 2013)
We describe a new species of the genus Gekko on the basis of 25 specimens from southern China and northern Vietnam. Gekko adleri sp. nov. is distinguished from the remaining congeners by a combination of the following characters: size moderate (SVL<80 mm); nares in contact with rostral; internasal single, smaller than supranasal; postmentals enlarged; interorbital scales between anterior corners of the eyes 27–36; dorsal tubercle rows 7–11; ventral scales between mental and cloacal slit 168–190; midbody scale rows 123–144; ventral scale rows 35–44; subdigital lamellae on first toe 11–14, on fourth toe 11–15; finger and toe webbing present at base; tubercles absent on upper surface of fore limbs; tubercles on tibia 0–8; precloacal pores 17–21 in males; postcloacal tubercle single; tubercles present on dorsal surface of tail base; subcaudals enlarged; dorsal surface of body with four or five narrow light bands between shoulder and sacrum.